Exosome-transmitted HSPA9 facilitates bortezomib resistance by targeting TRIP13/USP1 signaling in multiple myeloma - Min Shi; Na Shen; Xiangyu Liu; Jiapei Yu; Xuxing Shen; Ying Chen; Yuan Xia; Lijuan Chen (Cell Communication and Signaling)
Abstract Background Resistance to the proteasome inhibitor bortezomib (BTZ) poses a formidable therapeutic challenge in multiple myeloma (MM). Our study aims to analyze the mechanism by which exosomes heat shock 70 kDa protein 9 (HSPA9) secreted by BTZ-resistant MM cells disseminate resistance to BTZ-sensitive MM cells. Methods The serum exosomes were identified by nanoparticle tracking analysis and transmission electron microscopy. Liquid chromatography-mass spectrometry and public databases were performed to screen exosomes HSPA9. Cell counting kit-8, western blotting and colony formation assay were used to detected the role of HSPA9 protein in vitro. Co-immunoprecipitation, immunofluorescence and protein truncation test experiments were used to determine the regulatory network of the HSPA9-USP1-TRIP13 complex. Optical imaging in vivo and xenograft mouse models were performed to investigate that exosomes HSPA9 promoted MM proliferation and BTZ resistance. Results We demonstrated that HSPA9 was highly expressed in serum exosomes and BTZ-resistant MM patients. Knockdown of HSPA9 significantly suppressed tumorigenesis and reversed BTZ resistance in vitro. As a downstream molecular of HSPA9, thyroid hormone receptor-interacting protein 13 (TRIP13) was also highly expressed in BTZ-resistant MM patients. Mechanistically, the carboxyl-terminal peptide-binding domain of HSPA9, provides a platform for recruiting the deubiquitinating enzyme ubiquitin-specific peptidase 1 (USP1), which prevents TRIP13 protein degradation. The HSPA9-USP1-TRIP13 complex exhibits stability in the cytoplasm, and its inhibition remarkably enhances BTZ resistance in vito. Conclusion Our findings propose a pioneering molecular regulatory network in which MM-cell-derived exosomes HSPA9 transmitted BTZ resistance through the USP1/TRIP13 signaling pathway. This research highlights exosomes HSPA9 as a promising target to overcome MM BTZ resistance.